Specificities of prison and its approximation with education in Paraná: brief notes from the literature review (Práxis Educativa, 2018)
This work has the objective of presenting studies that deal with the educational practice facing the specificity of the prison space. Its possibilities and limits are observed and approximations of the context of prisons in Paraná are identified. For this, the literature review was chosen, and it was possible to point out and select the productions related to the investigations on education in prisons, outlining its conditions and supporting documents. The search of the documents dealt with the publications in two phases: from 1996 to 2006 and 2007 to 2017. The selection and classification of the documents were defined from the following categories of analysis: Prison Education, Educational Legislation, Legislation and Prison Public Policies. Thus, of the eleven publications selected, education was observed with a function of justification of permanence and maintenance of the prison sentence with a view to the progressive and reducing aspect of the damages caused by the current prison conditions. Keywords: Prison. Education. Paraná.